TEACHER PROFESSIONALISM AND COMPETENCE IN THE PERSPECTIVE OF CONTEMPORARY ISLAMIC EDUCATION - Anisaturrizqi, Rita; Saputra, Muhammad Akhyar Aji; Hanifiyah, Fitriyatul (FAJAR Jurnal Pendidikan Islam, 2025)
This study aims to examine the focus of scientific studies related to teacher competence and professionalism in the perspective of education, especially in the context of Islamic education. The results of the study show that the themes of teacher professionalism and teacher competence are the center of attention in the literature, which is closely linked to important aspects such as pedagogic competence, educator professional ethics, quality of education, and the social image of teachers. In addition, the analysis of temporal developments shows a shift in focus from fundamental issues to more contextual and applicative topics, such as strengthening writing competence and improving the quality of public perception of educational institutions. These findings show that the development of teacher professionalism cannot be separated from the integration of Islamic values, as well as the importance of building the character of educators who excel spiritually, morally, and intellectually. This study is expected to be a strategic reference for curriculum development, improving the quality of Islamic education, and forming ideal teachers in the perspective of Islamic values.